Medical associations’ guidance on caring for patients experiencing incarceration in the United States - Nicholas V. Nguyen; Tyler A. Nguyen; Kathleen M. Akgün; Amen Sergew; Matthew F. Griffith; Erin S. DeMartino (PLoS ONE, 2025)
The United States has one of the highest incarceration rates in the world. Carceral status can complicate clinical encounters in community and academic settings for an already medically vulnerable population. While it is likely physicians will encounter patients experiencing incarceration in their practice, there are few educational opportunities dedicated to ensuring delivery of healthcare that protects patient dignity, autonomy, and privacy. Professional medical associations can play a role in filling this physician knowledge gap. The goal of this analysis is to catalogue and analyze the current landscape of official medical association documents addressing healthcare of people experiencing incarceration. A systematic Internet search was conducted of American Medical Association House of Delegates associations and their existing documents. Out of 116 associations included in the systematic search, 16 groups published materials on incarceration. From these 16 associations, 44 documents were identified and coded thematically. Documents served four main purposes: education on incarceration (28/44), clinical guidance (25/44), logistical guidance (27/44), and policy advocacy (30/44). Common topics included medical conditions of people experiencing incarceration, patient factors antecedent to incarceration, and specialty or population-specific information. Few medical associations have published material on incarceration and the paucity of pragmatic clinical guidance was particularly pronounced. A lack of resources from medical associations can lead to variability and lapses in best healthcare practices when treating patients experiencing incarceration. Medical associations should consider developing guidance for clinicians to maximize this patient population’s autonomy and dignity.